Ink preparation for direct-ink-writing (3D printing) of a bio-based material for green buildings - Chew, Zhi Yong (Nanyang Technological University, 2020)
For centuries, concrete has been the material of choice for construction our buildings. However, the process of making concrete is requires huge amounts of energy and causes harmful effects to mankind and the natural environment. With agricultural by-products being discarded as waste, we can potentially make use of these by-products which are rich in cellulose and lignin that can act as substrate for the fungi to colonise. One such agricultural by-product is bamboo, a material which has a very fast growth rate and possesses good strength. The fungi secrets enzymes that can break down cellulose into simpler product that it can feed on. This produces a web-like mycelium network that can bind the substrate to form composite that has a variety of application. Currently, reasonable success has been achieved in fabricating these mycelium-based composite for use in the construction industry. Chitosan on the other hand is a polysaccharide that is commonly found in shellfish. Chitosan is used as biopesticide and bandages to help reduce bleeding. When mixed with acetic acid, chitosan turns into a gel-like substance. This gel-like substance can be mixed with bamboo-based mycelium to create a bio-ink for green buildings. The bio-ink is optimised with various concentrations (2 wt% and 3 wt%) of chitosan being mixed with bamboo-based mycelium spawn of different substrate size (1 mm and 500 μm) at different ratios (50:50, 60:40, 70:30) further grown under different pH conditions (pH 4, 5,6). From the results generated, it showed the mycelium growth rate favours higher pH conditions, lower chitosan to mycelium ratio, smaller substrate size and higher concentration of chitosan. The compression test showed that higher mycelium growth causes the compression strength to drop. However, the bio-ink did not show much success in being extruded. Only the horizontal hand extrusion from a syringe with a cut off nozzle manage to extrude a single filament. Therefore, more optimisation to the viscosity of the chitosan gel must be done to improve the extrusion process of the bio-ink.